Interdisciplinary and Social Nature of Engineering Practices Philosophy, Examples and Approaches - Zambroni de Souza, Antonio Carlos; Verkerk, Maarten J.; Ribeiro, Paulo Fernando; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book covers practical and philosophical aspects of Engineering, paying special attention to the social impacts of emerging technologies. Some fundamentals of philosophy of technology are introduced followed by social, economic, and environmental discussion and implications in different disciplines. Each chapter provides insights on the responsibilities involved in the design of engineering projects. The examples presented combine concepts about the impacts of Engineering in society at the same time that incorporates new technological models, yielding an innovative approach about the topics. .
Chapter 1: Introduction Complexity - Diversity - Coherence- Meaningfulness -- Chapter 2: Key Concepts for Frameworks: Values, Aspects, Normativity and Enkaptic Structures -- Chapter 3: Towards a Holistic Design for Engineering Infrastructures of the Future -- Chapter 4: The Social Dimension - Engineering and Social Welfare -- Chapter 5: Industrial Innovation Practices Breakthrough by Process Intensification -- Chapter 6: Renewables and Sustainability -- Chapter 7: Economics, Regulatory Aspects -- Chapter 8: Statistics and System Prediction.
Keywords: Industrial engineering; Production engineering; Ethics; Industrial and Production Engineering; Moral Philosophy and Applied Ethics; Engineering -- Philosophy